Determination of Trolox equivalent antioxidant capacity in berries using amperometric tyrosinase biosensor based on multi-walled carbon nanotubes - Frangu, Arber; Ashrafi, Amir M; Sýs, Milan; Arbneshi, Tahir; Metelka, Radovan; Adam, Vojtech; Vlček, Milan; Richtera, Lukas (MDPI, 2020)
In this contribution, Trolox equivalent antioxidant capacity (TEAC) was determined in various berries using carbon paste tyrosinase biosensor with multi-walled carbon nanotubes (MWCNTs), coated with Nafion((R)) layer. Electrochemical behaviour of the biosensor and influence of MWCNTs on carbon paste surface were studied with respect to the sensitive amperometric detection of total content of phenolic compounds in berries, expressed as concentration equivalent of Trolox. After optimization of key instrumental and electroanalytical parameters, the biosensor was used for determination of TEAC in blackberries, blueberries, cranberries, raspberries and strawberries by method of multiple standard additions. Electrochemical TEAC assays corresponded well with results obtained by spectrophotometric 1,1-diphenyl-2-picrylhydrazyl radical method, known as DPPH assay. Obtained values were compared with those listed in the National Nutrient Database for additional antioxidant capacity assays as well.
Stanovení Trolox ekvivalent antioxidační kapacity lesních plodů pomocí amperometrického tyrosinázového biosenzoru využívající vícestěnné uhlíkové nanotrubice
Keywords: amperometry; ascorbic acid; berries; biosensor; multi-wall carbon nanotubes; carbon paste electrode; tyrosinase; Trolox; antioxidant capacity; amperometrie; kyselina askorbová; biosenzor; vícestěnné uhlíkové nanotrubice; uhlíková pastová elektroda; tyrosináza; Trolox; antioxidační kapacita